Bioactive Molecules in Food - Mérillon, Jean-Michel; Ramawat, Kishan Gopal (Reference Series in Phytochemistry,, 2019)
This reference work provides comprehensive information about the bioactive molecules presented in our daily food and their effect on the physical and mental state of our body. Although the concept of functional food is new, the consumption of selected food to attain a specific effect existed already in ancient civilizations, namely of China and India. Consumers are now more attentive to food quality, safety and health benefits, and the food industry is led to develop processed- and packaged-food, particularly in terms of calories, quality, nutritional value and bioactive molecules. This book covers the entire range of bioactive molecules presented in daily food, such as carbohydrates, proteins, lipids, isoflavonoids, carotenoids, vitamin C, polyphenols, bioactive molecules presented in wine, beer and cider. Concepts like French paradox, Mediterranean diet, healthy diet of eating fruits and vegetables, vegan and vegetarian diet, functional foods are described with suitable casestudies. Readers will also discover a very timely compilation of methods for bioactive molecules analysis. Written by highly renowned scientists of the field, this reference work appeals to a wide readership, from graduate students, scholars, researchers in the field of botany, agriculture, pharmacy, biotechnology and food industry to those involved in manufacturing, processing and marketing of value-added food products.